2019
DOI: 10.1002/jcb.28477
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization and Overexpression of Smoothened in Pancreatic and Colorectal Cancers

Abstract: Smoothened (SMO) is a significant signalling protein which functions as a key transducer for the hedgehog signalling pathway, an important signalling mechanism with key roles in development and oncogenesis. The correlation of expression dynamics of SMO with pancreatic and colorectal cancer genesis has been known but with ambiguity. Therefore, in this study, we investigated messenger RNA (mRNA) and protein expression of SMO in pancreatic and colorectal cancers in our population and assessed relationship with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Total RNA was extracted by the Trizol method (Invitrogen Waltham, MA, United States)[ 20 ]. The absorbance at A260/280 of 1.8-2 was considered “pure” for RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted by the Trizol method (Invitrogen Waltham, MA, United States)[ 20 ]. The absorbance at A260/280 of 1.8-2 was considered “pure” for RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Kumar et al also emphasized the essential role of SHH signaling in the development and metastasis of pancreatic cancer cells [80]. Niyaz et al mentioned that dysregulated SMO could be a therapy target in pancreatic cancers [81].…”
Section: Shh In Pancreatic Cancermentioning
confidence: 99%
“…Regan et al found that the SHH signaling in colon cancer stem cells includes SHH-dependent, non-canonical PTCH1-dependent, and GLI-independent pathways, suggesting that non-canonical SHH signaling positively affects WNT signaling and is essential for the survival of colon cancer stem cells [111]. Niyaz et al suggested that dysregulated SMO could be as a treatment target of colon cancer [81]. [114][115][116][117][118][119].…”
Section: Colon Cancermentioning
confidence: 99%
“…SMO regulated EMT, invasion and migration of pancreatic cancer stem cells [ 95 ]. Thus, the dysregulated SMO in pancreatic cancers could be a therapeutic target [ 96 ].…”
Section: Smo and Pancreatic Cancermentioning
confidence: 99%
“…GDC-0499 is used to inhibit and modulate cellular plasticity and invasiveness in colorectal cancer [ 111 ]. Therefore, SMO could be a potential treatment target for colon cancer [ 96 ].…”
Section: Smo and Colon Cancermentioning
confidence: 99%